Tides Measurement and Tidal Analysis at Jakarta Bay - Hollanda Arief Kusuma; Muhammad Zainuddin Lubis; Nadya Oktaviani; Dwi Eny Djoko Setyono (Journal of Applied Geospatial Information, 2021)
Tides observation conducted for these purposes such as real-time depth of water, determination mean sea level and other tidal datums to establish a system of tidal benchmarks and data for production of tide and tidal current predictions. Center for Marine and Coastal Mapping – Geospatial Information System used water level and tides data mainly to correct the water depth measurement to chart datum. This study uses sea level observation data conducted from 20th February 2018 until 4th April 2018 at Marina Batavia, Jakarta. This study found that tidal types at this location is mixed diurnal using formzahl number. Astronomical and shallow water possible constituent were derived from the harmonic analysis. Fourier analysis gives clearly visual interpretation in frequency perspective. Several constituents inseparable because of short duration records.